Modelling the Influence of Filter Structure on Efficiency nd Pressure Drop in Knitted Filters - Mullins, Benjamin; King, Andrew; Braddock, R. (Modelling and Simulation Society of Australia and New Zealand Inc., 2011)
Fibrous filters are used extensively in a range of applications, including process engineering, automotive filtration and for worker (respiratory) protection. These filters are usually a felted, nonwoven structure of randomly arranged fibres. However, a special class of such filters exists - knitted filters. These filters are advantageous for many applications, as their knitted structure imparts significant mechanical strength. The structure of the fibres in such filters can be described by the classical strophoid equation. There has been relatively little study on the pressure drop and efficiency of such filters. This work has developed a geometric model of a knitted metal filter, by applying the strophoid equation. The geometric model thus allows a range of geometries to be generated, based on the strophoid variables, and also fibre/wire diameter, then the knits layered at a given bulk porosity (packing density), to create a geometry of desired properties. The geometric model outputs can then be coupled with a novel computational fluid dynamics (CFD) model for fibrous filtration (developed by the authors). This then allows, the relationship between the aforementioned structural properties and critical filter properties such as particle capture efficiency and pressure drop to be investigated. This work examined the pressure drop and efficiency of a knitted filter geometry at 3 different packing densities. The CFD results were compared to classical single fibre efficiency theory for conventional fibrous filters. The CFD results showed increased capture efficiency and pressure drop compared to fibrous filter theory.